Full-field eigenstrain reconstruction for the investigation of residual stresses in finite length weldments - Uzun, F; Lee, TL; Wang, ZI; Korsunsky, AM (Elsevier, 2024)
The reconstruction of welding residual stresses has been performed based on the assumption of continuous processing conditions, owing to the limitations of reconstruction methods. This assumption prevents the attainment of a comprehensive understanding of mechanical deformations in the entire weld zone. The voxel-based eigenstrain (inherent strain) reconstruction method emerges as an appropriate approach for the full-field reconstruction of residual stresses in finite length weldments without such assumption. The innovative reconstruction capability of this advanced method is presented in this study, aiming to comprehend all components of residual stresses and eigenstrains in finite length weldments with discontinuous processing properties using only a single component of experimental data belonging to a limited portion of the specimen. Numerical experiments were conducted to develop the tools. These tools were validated using a case study employing experimental data obtained through contact profilometry measurements from the surface of discharge machine cutting (minimally disturbing cutting) in a bead-on-plate weldment of Inconel alloy 740H designed for ultra-supercritical power generation. The reconstructed two components of normal residual stresses that do not align with the available experimental data were validated by independent neutron diffraction strain scanning quantifications. Furthermore, the reconstruction of residual stresses in the intact component prior to cutting was carried out using the eigenstrains associated with the post-cut state of the weldment.